Education on the Utilization of Stingless Bees as Potential Natural Pollinators for Bitter Gourd Plants - Phika ainnadya hasan; Andi Gita Maulidyah Indraswari Suhri; Andi Aris Mattunruang; Muhammad Athar Asmas; A Hasdiansyah; Wiwik Wiji Astuti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
his activity aims to provide solutions to the problems faced by the community in the agricultural sector. In this case, the help of pollination by stingless bees is a solution to the quality and quantity of agricultural crop yields, especially bitter melon plants grown by the community. The selection of stingless bees as pollinating agents is based on safety and convenience reasons for the community in participating in a series of activities. These bees are adaptive and easy to manage. The activity method is participatory action research (PAR) which actively involves the community from the preparatory stage, the process, to the final stage. Activity evaluation includes context, input, process, and product. The result of this activity is that the community understands the technique of using pollinating bees to optimize bitter melon crop yields. Through this activity the community also understands the importance of maintaining bee populations in nature. The positive impact that can be expected from this activity is an increase in the quality and quantity of bitter melon yields in the form of fruit size, number of fruit, and number of seeds. Furthermore, the community took the initiative to plant other types of agricultural crops and reuse stingless bees as the main pollinating agent.